2023
DOI: 10.1186/s12933-023-01806-7
|View full text |Cite
|
Sign up to set email alerts
|

The right ventricular dysfunction and ventricular interdependence in patients with DM: assessment using cardiac MR feature tracking

Abstract: Background To investigate the difference of right ventricular (RV) structural and functional alteration in patients with diabetes mellitus (DM) with preserved left ventricular ejection fraction (LVEF), and the ventricular interdependence in these patients, using cardiac MR (CMR) feature tracking. Methods From December 2016 to February 2022, 148 clinically diagnosed patients with DM who underwent cardiac MR (CMR) in our hospital were consecutively r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Several studies have revealed that the T2DM group had a signi cantly lower RV GLS than the control group. Further, RV dysfunction was an important component of diabetic cardiomyopathy [10,17]. In the current study, the T2DM (AR−) group had a low RV global and regional longitudinal strain.…”
Section: Rv Dysfunction and Pathophysiological Mechanisms In T2dmmentioning
confidence: 52%
See 2 more Smart Citations
“…Several studies have revealed that the T2DM group had a signi cantly lower RV GLS than the control group. Further, RV dysfunction was an important component of diabetic cardiomyopathy [10,17]. In the current study, the T2DM (AR−) group had a low RV global and regional longitudinal strain.…”
Section: Rv Dysfunction and Pathophysiological Mechanisms In T2dmmentioning
confidence: 52%
“…Due to the predominance of longitudinal subendocardial myocytes, longitudinal shortening accounts for approximately 75% of RV contractions [20,21]. Therefore, the RV longitudinal strain was a good indicator of RV dysfunction and good reproducibility in patients with diabetes combined with circumferential strain [10,22,23]. Further, another study found that the deterioration of RV performance was observed in the basal and apical segments of the RV free wall in asymptomatic patients with diabetes [19].…”
Section: Rv Dysfunction and Pathophysiological Mechanisms In T2dmmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in line with the disparities observed in RVGCS and RVGLS among individuals with PH in the RVEF ≥ 50% category compared with controls in a study by de Siqueira et al 22 Advances in MRI technology have enabled cardiologists to use MRI-FT-derived myocardial strain as a means of early and sensitive detection of RV dysfunction across various disease profiles. 23,24 Studies have demonstrated that RV function serves as a significant prognostic indicator for patients with PH. 3,25 Furthermore, several studies have reported the correlation between myocardial strain parameters and the prognosis of patients with PH.…”
Section: Discussionmentioning
confidence: 99%